Impact fretting wear behavior of cemented carbide impact needle with surface modification - Shuiqing Liu; Haoran Xu; Jinyuan Fu; Silin Liu; Xu Han (Materials & Design)
High-current pulsed electron beam (HCPEB) treatment significantly enhances the wear resistance of WC-Co cemented carbide impact needles under high-frequency and micro-impact amplitude wear conditions, which are common in micro-nano mechanical systems. Quantitatively characterizing the effect of WC-Co on stress–strain relationships based on real microstructures and revealing the mechanisms of WC-Co surface modification by HCPEB treatment present certain challenges. Through modeling and experimental studies, the distribution of residual thermal stress (RTS) and the phase transition dependence under external stress on the wear resistance of HCPEB-modified WC-Co cemented carbide impact needles were quantified and resolved. It was discovered that HCPEB treatment reduces the proportion of recrystallization and recovery structures while increasing the content of grain deformation structures. The evolution of the stress field and microhardness along the depth of the microsurface reflects the adjustment process of HCPEB treatment on the microsurface properties of cemented carbide in the direction of electron incidence. Wear test results showed that after 300 million cycles, the wear volume of the impact needle treated with HCPEB was reduced by 71.4% compared to the untreated specimens, indicating that optimizing the wear resistance of materials by adjusting internal stresses to external loads and phase change processes is feasible.